Molecular Pathways: Targeting the Dependence of Mutant RAS Cancers on the DNA Damage Response - Grabocka, Elda (Clin Cancer Res, 2014)
Of the genes mutated in cancer, RAS remains the most elusive to target. Recent technological advances and discoveries have greatly expanded our knowledge of the biology of oncogenic Ras and its role in cancer. As such, it has become apparent that a property that intimately accompanies RAS-driven tumorigenesis is the dependence of RAS mutant cells on a number of non-oncogenic signaling pathways. These dependencies arise as a means of adaptation to Ras-driven intracellular stresses and represent unique vulnerabilities of mutant RAS cancers. A number of studies have highlighted the dependence of mutant RAS cancers on the DNA damage response and identified the molecular pathways that mediate this process including signaling from wild-type Ras isoforms, ATR/Chk1, and DNA damage repair pathways. Here we review these findings, and discuss the combinatorial use of DNA damaging chemotherapy with blockade of wild-type H- and N-Ras signaling by farnesyltransferase inhibitors, Chk1 inhibitors, or small molecule targeting DNA damage repair as potential strategies through which the dependence of RAS cancers on the DNA damage response can be harnessed for therapeutic intervention.